Effectiveness of Law Enforcement in Eradicating Gambling Crimes Committed Online in Indonesia - Harefa, Arianus (PT. Hafasy Dwi Nawasena, 2024)
The crime of online gambling is currently very worrying and damaging the joints of the life of the Indonesian people. In the development of science and technology, which is quite rapid, it has a negative impact on the reality of people's lives to be used as a means of playing gambling with the aim of making a profit without having to work hard. The impact of online gambling crimes causes social, economic, legal problems, financial losses, damages physical and mental health, disrupts personal and family relationships, and has the potential to commit new criminal acts. For this reason, law enforcement in combating online gambling is very necessary. Therefore, this research uses normative legal research or library research. While the research approach is statute approach, case approach, and conceptual approach. Then, to analyze the data, qualitative data analysis is used descriptively, logically, systematically to answer existing problems. The results show that law enforcement in the eradication of online gambling in Indonesia requires adequate measures through stricter supervision and enforcement of online gambling players, increased cooperation between law enforcement agencies and online platforms to monitor and identify illegal gambling activities, and massive counseling to the public about the risks and negative impacts of online gambling. In addition, to increase the capacity of investigators in addressing online gambling cases through training and skills development should be considered. And providing easier access for the public to report online gambling cases, and also cooperation with the provision of internet services to block illegal gambling sites to assist and prevent online gambling crimes in Indonesia